Pemanfaatan Disposable Diaper Waste Dengan Bahan Tambah Naphthalene Formaldehyde Sulfonate Menjadi Paving block Dalam Upaya Minimisasi Limbah Guna Mereduksi Pencemaran Lingkungan - Sari, Mayang; Ardiatma, Dodit; Ilyas, Nur Ilman (Jurnal Pelita Teknologi, 2024)
This study aims to determine the best classification and composition of paving blocks with the addition of disposable diaper waste, evaluated based on the compressive strength and water absorption of the paving blocks according to SNI 03-0691-1996. The study also examines the effect of varying amounts of disposable diaper waste on the compressive strength and water absorption tests, and compares the quality of paving blocks made with disposable diaper waste to commercial paving blocks. The research method used is an experimental approach with a quantitative approach. The materials used for producing the paving blocks include cement, sand, water, disposable diaper waste, and the additive Naphthalene Formaldehyde Sulfonate. Samples were tested to determine the relationship between the physical and mechanical properties with the material composition, in accordance with the quality of the paving blocks produced based on SNI 03-0691-1996. Based on this study, the optimal composition for compressive strength is the addition of 10 grams of disposable diaper waste, which resulted in a compressive strength of 36.76 MPa, meeting the SNI 03-0691-1996 standard quality A. For water absorption, the best composition is the addition of 5 grams of disposable diaper waste, showing the lowest water absorption of 1.41%, also meeting the standard quality A. Diterima: 8 Desember 2025.